High affinity of recombinant DJ-1 (PARK7) protein to Ni-NTA - Mussakhmetov, A.; Utepbergenov , D.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2022)
The DJ-1 protein also known as Parkinson disease protein 7 (PARK7) is a glyoxalase associated with hereditary form of Parkinson’s disease. Glyoxalase DJ-1 consists of 189 amino acids and has a molecular weight of 20 kDa. The physiological role of DJ-1 is unclear but recent evidence suggest that it can detoxify reactive electrophiles formed in glycolysis. Expression and purification of the recombinant DJ-1 protein in Escherichia coli revealed an abnormally high affinity of rDJ-1 for Ni-NTA, which was accompanied by a color change of Ni-NTA from blue to blue-violet. rDJ-1 formed the strong complex with Ni-NTA, which was destroyed only by 2400 mM imidazole. Experiments with the mutant DJ-1 protein containing the Cys106Ser substitution confirmed the key role of cysteine at position 106 for the formation of this complex. The discovered phenomenon shows the potential of using the DJ-1-tag as a protein tag for obtaining high-purity protein preparations and for bioanalytical applications.